Ethical Dilemmas in Physicians’ Consultations with COPD Patients - Sigurgeirsdottir,Jonina; Halldorsdottir,Sigridur; Arnardottir,Ragnheidur Harpa; Gudmundsson,Gunnar; Bjornsson,Eythor Hreinn (International Journal of Chronic Obstructive Pulmonary Disease, 2022)
Jonina Sigurgeirsdottir,1,2 Sigridur Halldorsdottir,3 Ragnheidur Harpa Arnardottir,3– 5 Gunnar Gudmundsson,1,6 Eythor Hreinn Bjornsson2 1Faculty of Medicine, University of Iceland, Reykjavik, Iceland; 2Pulmonary Department, Reykjalundur Rehabilitation Center, Mosfellsbaer, Iceland; 3Faculty of Graduate Studies, School of Health Sciences, University of Akureyri, Akureyri, Iceland; 4Department of Rehabilitation, Akureyri Hospital, Akureyri, Iceland; 5Department of Medical Sciences, Respiratory-, Allergy- and Sleep Research, Uppsala University, Uppsala, Sweden; 6Department of Respiratory Medicine and Sleep, Landspitali University Hospital, Reykjavik, IcelandCorrespondence: Jonina Sigurgeirsdottir, Pulmonary Department, Reykjalundur Rehabilitation Center, Furubyggd 28, Mosfellsbaer, 270, Iceland, Tel +354 6261740, Email jonina@reykjalundur.isAim: This phenomenological study was aimed at exploring principal physicians’ (participants’) experience of attending to COPD patients and motivating their self-management, in light of the GOLD clinical guidelines of COPD therapy.Methods: Interviews were conducted with nine physicians, who had referred patients to PR, five general practitioners (GPs) and four lung specialists (LSs). The interviews were recorded, transcribed, and analyzed through a process of deconstruction and reconstruction.Results: The participants experienced several ethical dilemmas in being principal physicians of COPD patients and motivating their self-management; primarily in the balancing act of adhering to the Hippocratic Oath of promoting health and saving lives, while respecting their patients’ choice regarding non-adherence eg, by still smoking. It was also a challenge to deal with COPD as a nicotine addiction disease, deal with patients’ denial regarding the harm of smoking and in motivating patient mastery of the disease. The participants used various strategies to motivate their patients’ self-management such as active patient education, enhancing the patients’ inner motivation, by ...